Integrating Religious Moderation into Islamic Education: A Conceptual and Practical - Haryono Haryono; Rizkan Rizkan (JPT : Jurnal Pendidikan Tematik, 2025)
This article discusses the importance of integrating the values of religious moderation in Islamic education as an effort to cultivate religious attitudes that are tolerant, inclusive, and uphold the values of peace. This study uses a conceptual and implementative approach to examine how the concept of religious moderation can serve as a foundation for curriculum development and the learning process in Islamic education. The discussion includes the definition of religious moderation, its theological foundations, relevance to the socio-religious context in Indonesia, as well as implementation strategies within formal educational settings. The article concludes with a reflection on the challenges and opportunities of applying the values of moderation in shaping students' character in the digital era.